Notes on channel capacity per unit cost - TIAN Da-gang (Tongxin xuebao)
For the computation of the capacity per unit cost,an extension of the basic theorem connect the capacity per unit cost with the capacity-cost function was made,and the single peak of the generalized capacity-cost function per unit cost was proved.Then,an algorithm to locate the optimal point of the generalized capacity-cost function per unit cost based on the single peak of the function was proposed.Meanwhile,it was proved that the computation of the capac-ity-cost function,which is a constrained channel capacity issue,can be expressed as a convex optimization,to which the objective function is self-concordant.The algorithm and its computational complexity were given.